Effect of Liquidity, Profitability, and Sales Growth on Capital Structure (in Manufacturing Companies) - Marlina, Marlina; Pinem, Dahlia; Hidayat, Nur Fatkhul (International Humanities and Applied Science Journal, 2020)
Abstract - This research was conducted to examine the effect of liquidity, profitability and sales growth on capital structure. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange. The technique of determining the sample using purposive sampling method. Selection of samples from 165 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018 resulted in 33 companies being accepted. Data analysis was performed using Microsoft Excel 2013 and hypothesis testing in this research used Panel Data Regression Analysis with the E-Views 9.0 program and a significance level of 5%. The results of the test were obtained (1) the liquidity stated by CR has no significant effect on the capital structure. (2) profitability stated by ROE has a significant positive effect on capital structure, (3) sales growth stated by SG has no significant positive effect on capital structure.Â Keywords: liquidity, profitability, sales growth, capital structure